The impact of artificial intelligence on human resource management practices: An investigation - Thandukwazi R. Ncube; Kusangiphila K. Sishi; Jane P. Skinner (SA Journal of Human Resource Management)
Orientation: This study investigates the transformative impact of artificial intelligence (AI) technologies on traditional human resource management (HRM) practices across key industries.